Ab initio calculation of spin fluctuation spectra using time-dependent density functional perturbation theory, plane waves, and pseudopotentials - Cao, K; Lambert, H; Radaelli, PG; Giustino, F (American Physical Society, 2018)
We present an implementation of time-dependent density functional perturbation theory for spin fluctuations, based on plane waves and pseudopotentials. We compute the dynamic spin susceptibility self-consistently by solving the time-dependent Sternheimer equation, within the adiabatic local density approximation to the exchange and correlation kernel. We demonstrate our implementation by calculating the spin susceptibility of representative elemental transition metals, namely bcc Fe, fcc Ni, and bcc Cr. The calculated magnon dispersion relations of Fe and Ni are in agreement with previous work. The calculated spin susceptibility of Cr exhibits a soft-paramagnon instability, indicating the tendency of the Cr spins to condense in an incommensurate spin density wave phase, in agreement with experiment.